Adolescent binge drinking disrupts normal trajectories of brain functional organization and personality maturation - Whelan, Robert; Bokde, Arun; Hongtao, Ruan; Zhou, Yunyi; Qiang, Luo; Robert, Gabriel H.; Desrivieres, Sylvane; Burke Quinlan, Erin; Liu, ZhaoWen; Banaschewski, Tobias; Bromberg, Uli; Büchel, Christian; et al. (My University, 2019)
Adolescent binge drinking has been associated with higher risks for the development of many health problems throughout the lifespan. Adolescents undergo multiple changes that involve the co-development processes of brain, personality and behavior; therefore, certain behavior, such as alcohol consumption, can have disruptive effects on both brain development and personality maturation. However, these effects remain unclear due to the scarcity of longitudinal studies. In the current study, we used multivariate approaches to explore discriminative features in brain functional architecture, personality traits, and genetic variants in 19-year-old individuals (n = 212). Taking advantage of a longitudinal design, we selected features that were more drastically altered in drinkers with an earlier onset of binge drinking. With the selected features, we trained a hierarchical model of support vector machines using a training sample (n = 139). Using an independent sample (n = 73), we tested the model and achieved a classification accuracy of 71.2%. We demonstrated longitudinally that after the onset of binge drinking the developmental trajectory of improvement in impulsivity slowed down. This study identified the disrupting effects of adolescent binge drinking on the developmental trajectories of both brain and personality.
Keywords: Adolescent binge drinking; Resting state; Personality; Genome; Co-development